2017
DOI: 10.1016/j.cell.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cellular Mechanisms Underlie Anti-CTLA-4 and Anti-PD-1 Checkpoint Blockade

Abstract: Summary Immune checkpoint blockade is able to achieve durable responses in a subset of patients, however we lack a satisfying comprehension of the underlying mechanisms of anti-CTLA-4 and anti-PD-1 induced tumor rejection. To address these issues we utilized mass cytometry to comprehensively profile the effects of checkpoint blockade on tumor immune infiltrates in human melanoma and murine tumor models. These analyses reveal a spectrum of tumor infiltrating T cell populations that are highly similar between tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
870
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,020 publications
(936 citation statements)
references
References 60 publications
(52 reference statements)
61
870
1
4
Order By: Relevance
“…3A), supporting recent observations that immune checkpoint blocking antibodies preferentially expand exhausted phenotype T-cells in both mice and man. 22 However, T-cell populations appeared functionally less exhausted in vistusertib treated tumour bearing mice, exhibiting lower expression of the exhaustion marker PD-1 (Fig. 3A-C).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…3A), supporting recent observations that immune checkpoint blocking antibodies preferentially expand exhausted phenotype T-cells in both mice and man. 22 However, T-cell populations appeared functionally less exhausted in vistusertib treated tumour bearing mice, exhibiting lower expression of the exhaustion marker PD-1 (Fig. 3A-C).…”
Section: Resultsmentioning
confidence: 95%
“…3). 22 In contrast, through pleiotropic effects to modulate Th1 promoting innate immune cytokines, and selectively enhance effector CD8 + T-cell viability, vistusertib was able to confer a less suppressive tumour microenvironment (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…38 Hence, the mechanism of action of anti-PD-1 therapy is to reverse the exhaustion of pre-existing tumor-residing T cells, thus improving their effector functions to carry out tumor regressions. 3941 Depending on the context and their sensitivity, if tumor-infiltrating T cells undergo adequate exposure to corticosteroids, then the benefits conferred by anti-PD-1 therapy may be diminished or completely lost. Endogenous and exogenous corticosteroids have been demonstrated to reduce antitumor immunity and counteract cancer immunotherapy in a murine autochthonous pancreatic ductal carcinoma model.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several studies have shown that anti-PD-1/PD-L1 and anti-CTLA-4 act through distinct mechanisms. 2,3 CTLA-4 interferes in the early stages of T cell activation by inhibiting stimulatory signaling that is required following antigen-T cell receptor (TCR) binding. Conversely, PD-1 is involved later in T cell activation and acts by attenuating TCR signaling following engagement with its ligands, PD-L1 or PD-L2.…”
Section: Introductionmentioning
confidence: 99%